To determine the equation of the line \( y = mx \) that describes the proportional relationship, we will need to find the slope \( m \) of the line. The slope is calculated by the change in \( y \) divided by the change in \( x \).
From the points given:
- \( (3, 1) \)
- \( (6, 2) \)
- \( (9, 3) \)
We can use any two points. Let's calculate the slope using the first two points \( (3, 1) \) and \( (6, 2) \):
\[ m = \frac{y_2 - y_1}{x_2 - x_1} = \frac{2 - 1}{6 - 3} = \frac{1}{3} \]
Now we have the slope \( m = \frac{1}{3} \).
Thus, the equation of the line passing through the origin with this slope is:
\[ y = \frac{1}{3}x \]
So, the final answer is:
\[ y = \frac{1}{3}x \]